2005
DOI: 10.1097/01.mib.0000158535.54428.a5
|View full text |Cite
|
Sign up to set email alerts
|

Increased Transduction of Human Intestinal Epithelial Cells by Adenoviral Vectors in Inflammatory Bowel Disease

Abstract: We conclude that intestinal epithelial cells from IBD patients are more readily transfected by standard adenoviral vectors than are those from control patients. These results suggest that targeting genes to inflamed intestine through the luminal route may be possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
2
4
0
Order By: Relevance
“…Ad5 and Ad5SHORT Transduction Studies in Differentiated and Undifferentiated Caco-2 Cells. As previously reported, , transduction of Caco-2 cells by adenoviral vectors was low. Application of the Ad5SHORT vectors led to further significant decrease in transduction efficiency.…”
Section: Resultssupporting
confidence: 65%
“…Ad5 and Ad5SHORT Transduction Studies in Differentiated and Undifferentiated Caco-2 Cells. As previously reported, , transduction of Caco-2 cells by adenoviral vectors was low. Application of the Ad5SHORT vectors led to further significant decrease in transduction efficiency.…”
Section: Resultssupporting
confidence: 65%
“…In the present study, LV-transduced cells in human explant samples were found primarily in the subepithelial region of the LP whereas in other colorectal explant studies using adenoviral vectors [42] transduction was commonly observed in the basolateral region. However, it is difficult to compare our data with other published studies as the cell tropism may differ between vectors.…”
Section: Discussionmentioning
confidence: 50%
“…To determine the biological effects of DRA, we also conducted in vivo experiments. Previous work has shown that normal mature intestinal epithelial cells are extremely resistant to transduction by adenovirus, whereas tissue from IBD patients is transduced significantly more readily than normal tissue [46]. Therefore, Ad-DRA was administered on days 1, 3, and 5 following the initial DSS treatment.…”
Section: Discussionmentioning
confidence: 99%